Effect of preset interfacial ZrB2 particles on the microstructure and properties of C/C-AlSi composites. (September 2021) - Feng, Wei; Tang, Chengwei; Liu, Lei; Chen, Jian; Zhang, Yang; Yao, Xiyuan; Zuo, Donglin; Liu, Feilong
ZrB2 particles were preset to the C-AlSi interface to improve oxidation resistance of C/C preform and adjust the microstructure of the interpenetrated C/C-AlSi composite prepared through pressure infiltration of eutectic AlSi into a fiber fabric based porous C/C skeleton. Micro-morphology investigations suggested that the AlSi textures were changed from dendritic to petals-like state, and the nano to micro-scale ZrB2 particles were dispersed into AlSi and affected the distribution of Al and Si nearby carbon. Tests demonstrated that C/C-AlSi have slight lower density and thermal expansion coefficient, and higher original compressive strength, while C/C-ZrB2 -AlSi composites presented an outstanding strength retention rate after thermal shock. Fracture and micro-morphology indicated that the influence of the preset ZrB2 to the interface of carbon and alloy greatly affected the generation and propagation of cracks, which determined the diverse compression behaviors of the composites before and after thermal shock.